MAGNITUD DE LA ECONOMÍA INFORMAL EN EL PERÚ Y EL MUNDO - Barragan Arqué, Paulino (2005)
In Peru the growth of the informal economy is associated to the population’s growth, the scarce growth of the economy and the shortage of work sources. It is calculated that the informal economy in our country is equivalent to 35% of the PBI and 60% of work. The informal economy is not an exclusive phenomenon of the developing countries. Today the globalization of the economy has evidenced that the practice of producing wealth and creating employment outside of the legal context is also a phenomenon of the developed world. The magnitude of the informal economy in the developing countries and in the developed countries doesn’t appear in the official statistics of the Bills, for what it is ignored with accuracy its measure and incidence on the National Economy, what constitutes a great limitation in the design of the economical policies, the fiscal policies and the tributary policies altogether.